An improved reference genome for Trifolium subterraneum L. provides insight into molecular diversity and intra-specific phylogeny - Shirasawa, Kenta; Moraga, Roger; Ghelfi, Andrea; Hirakawa, Hideki; Nagasaki, Hideki; Ghamkhar, Kioumars; Barrett, Brent A.; Griffiths, Andrew G.; Isobe, Sachiko N. (Frontiers in Plant Science, 2023)
Subterranean clover (Trifolium subterraneum L., Ts) is a geocarpic, self-fertile annual forage legume with a compact diploid genome (n = x = 8, 544 Mb/1C). Its resilience and climate adaptivity have made it an economically important species in Mediterranean and temperate zones. Using the cultivar Daliak, we generated higher resolution sequence data, created a new genome assembly TSUd_3.0, and conducted molecular diversity analysis for copy number variant (CNV) and single-nucleotide polymorphism (SNP) among 36 cultivars. TSUd_3.0 substantively improves prior genome assemblies with new Hi-C and long-read sequence data, covering 531 Mb, containing 41,979 annotated genes and generating a 94.4% BUSCO score. Comparative genomic analysis among select members of the tribe Trifolieae indicated TSUd 3.0 corrects six assembly-error inversion/duplications and confirmed phylogenetic relationships. Its synteny with T. pratense, T. repens, Medicago truncatula and Lotus japonicus genomes were assessed, with the more distantly related T. repens and M. truncatula showing higher levels of co-linearity with Ts than between Ts and its close relative T. pratense. Resequencing of 36 cultivars discovered 7,789,537 SNPs subsequently used for genomic diversity assessment and sequence-based clustering. Heterozygosity estimates ranged from 1% to 21% within the 36 cultivars and may be influenced by admixture. Phylogenetic analysis supported subspecific genetic structure, although it indicates four or five groups, rather than the three recognized subspecies. Furthermore, there were incidences where cultivars characterized as belonging to a particular subspecies clustered with another subspecies when using genomic data. These outcomes suggest that further investigation of Ts sub-specific classification using molecular and morpho-physiological data is needed to clarify these relationships. This upgraded reference genome, complemented with comprehensive sequence diversity analysis of 36 cultivars, provides a platform for future gene functional analysis of key traits, and genome-based breeding strategies for climate adaptation and agronomic performance. Pangenome analysis, more in-depth intra-specific phylogenomic analysis using the Ts core collection, and functional genetic and genomic studies are needed to further augment knowledge of Trifolium genomes.